After continents divide: Comparative phylogeography of reef fishes from the Red Sea and Indian Ocean - Di Battista, Joseph; Berumen, M.; Gaither, M.; Rocha, L.; Eble, J.; Choat, J.; Craig, M.; Skillings, D.; Bowen, B. (Blackwell Publishing, 2013)
Aim: The Red Sea is a biodiversity hotspot characterized by a unique marine fauna and high endemism. This sea began forming c. 24 million years ago with the separation of the African and Arabian plates, and has been characterized by periods of desiccation, hypersalinity and intermittent connection to the Indian Ocean. We aim to evaluate the impact of these events on the genetic architecture of the Red Sea reef fish fauna. Location: Red Sea and Western Indian Ocean. Methods: We surveyed seven reef fish species from the Red Sea and adjacent Indian Ocean using mitochondrial DNA cytochrome c oxidase subunit I and cytochrome b sequences. To assess genetic variation and evolutionary connectivity within and between these regions, we estimated haplotype diversity (h) and nucleotide diversity (p), reconstructed phylogenetic relationships among haplotypes, and estimated gene flow and time of population separation using Bayesian coalescent-based methodology. Results: Our analyses revealed a range of scenarios from shallow population structure to diagnostic differences that indicate evolutionary partitions and possible cryptic species. Conventional molecular clocks and coalescence analyses indicated time-frames for divergence between these bodies of water ranging from 830,000 years to contemporary exchange or recent range expansion. Colonization routes were bidirectional, with some species moving from the Indian Ocean to the Red Sea compared with expansion out of the Red Sea for other species. Main conclusions: We conclude that: (1) at least some Red Sea reef fauna survived multiple salinity crises; (2) endemism is higher in the Red Sea than previously reported; and (3) the Red Sea is an evolutionary incubator, occasionally contributing species to the adjacent Indian Ocean. The latter two conclusions - elevated endemism and species export - indicate a need for enhanced conservation priorities for the Red Sea. © 2013 Blackwell Publishing Ltd.